Finding suitable locations for live campaigns using different machine learning techniques - Qudar, Mohiuddin Md. Abdul; Tazrin, Tahrat; Khanam, Kazi Zainab (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.